Fractures in the education–economy relationship: the end of the skill bias technological change research programme?. (2nd July 2018) - Lauder, Hugh; Brown, Phillip; Cheung, Sin-Yi
Abstract: This paper undertakes a critical theoretical and empirical analysis of the traditional approach to analysing the education–economy relationship: skill bias technological change theory. It argues that while leading skill bias theorists have sought to address some of the anomalies that the theory confronts, there remain key data patterns that the theory cannot address. We suggest an alternative account that takes a broader political economy perspective.